Long Acting Animal Health Drug Products Fundamentals and Applications - Rathbone, Michael J.; McDowell, Arlene (Advances in Delivery Science and Technology, 2013)
This authoritative book is a comprehensive guide on the theories, applications, and challenges associated with the design and development of long acting veterinary formulations.  The volume acts as a reference to the animal health formulation scientist and contains chapters written by some of the leading experts in the field.  In addition it offers additional details through a mixture of figures, tables, and references to provide information not found in other similar texts.   The book covers everything a student or a formulation scientist in industry or academia needs to know about this unique drug delivery field. It provides an overview of the fundamental science necessary for the rational design and development of veterinary animal health products, and provides in-depth descriptions of the technologies that are currently commercially available for the prolonged delivery of drugs to animals.   Long Acting Animal Health Drug Products: Fundamentals and Applications will be indispensible to scientists interested in the science and technology of drug delivery to animals and be essential for those developing long acting delivery systems for farmed and companion animals.